Myeloproliferative neoplasms biology and therapy - Verstovsek, Srdan; Tefferi, Ayalew (Contemporary hematology, 2010)
This succinct resource provides an ideal balance of the biology and practical therapeutic strategies for classic and non-classic BCR-ABL-negative myeloproliferative neoplasms. Utilizing current World Health Organization nomenclature, classification, and diagnostic criteria, international experts have assembled to convey the most up-to-date knowledge in this rapidly evolving field. The opening chapters cover the diagnosis and classification, genetics, cytogenetic findings, and prognostic factors of MPNs. Further chapters explore therapies specific to the different disease entities, including polycythemia vera, essential thrombocytopenia, myelofibrosis, and eosinophilic disorders, and mastocytosis. Unique areas of discussion include JAK2 inhibitor therapy, hematopoietic stem cell transplantation, and blastic transformation. A valuable reference for practicing hematologists, this forefront book enriches our understanding of recent discoveries and their impact on conventional and investigational treatments.